The Role of Electrification in the Decarbonization of the Energy Sector in Portugal - Martins, Fernando (2022)
Climate change already affects all inhabited regions of the world, with human influence contributing to many observed changes in climate extremes and to mitigate this trend, important decisions have been taken by different world organizations and countries to achieve global net-zero emissions. At the European Union level (EU27 countries), two of the main pillars for achieving carbon neutrality are: (1) The “Energy Efficiency First principle” in the formulation of energy policy and in taking relevant investment decisions and (2) the electrification of the energy sector, supported by generating electricity through endogenous renewable energy sources. In this context, a comprehensive review was carried out on what has been developed by the scientific community and main international energy organizations on the electrification of the energy sector. Additionally, with the purpose of better understanding the state of the art of a country regarding the decarbonization process, the Portuguese energy vectors were identified in terms of which ones can and should be electrified by 2050, based on the data available from Eurostat (2019). Portugal is a country highly dependent on imported energy (78%), where the largest energy vector is from oil and petroleum products (68%) mostly used in the transport sector, where the electrification of the sector will be increased gradually until 2050. However, other decarbonized solutions, such as biofuels and synthetic (green) fuels cannot be ruled out and should be the subject of future work and considered for the decarbonization goals to be achieved in 2050. The main conclusions reflect that there is still a long way to go, much like the rest of the world, as it is necessary to electrify the equivalent to almost all the energy presently imported by Portugal, a tough challenge considering the need for its generation to be decarbonized. In this context, energy efficiency must play an equivalently important role to significantly reduce current energy demand, leading to more cost-effective and resilient energy services